The Influence of Christian Religious Education, Ministry and Pastoral Counseling on The Moral Development of Youth in The Indonesian Pentecostal Church Sector 7 Jakarta - Tambunan, Daulat Marulitua; Iskandar, Ferdinand (LP. Ma'arif Janggan Magetan, 2024)
This study aims to comprehensively analyze the influence of Christian Religious Education (PAK), counseling, and pastoral ministry on the moral development of youth in the Indonesian Pentecostal Church Sector 7 Jakarta. The moral development of youth is a key aspect in the formation of Christian character and the future desires of the church, which are strongly influenced by structured educational and pastoral interventions. This study uses a quantitative approach with a survey design, where data is collected through a questionnaire that is distributed to a sample of church youth representatives. The results of the study show that PAK, counseling, and pastoral services have a positive and significant influence on the moral development of youth, both individually and simultaneously. The contribution of PAK (X1), pastoral ministry (X2), and pastoral counseling (X3) to moral development (Y) in the Indonesian Pentecostal Church Sector 7 Jakarta is very high, with a determination coefficient value (R²) of 0.969 or 96.9%. This means that this third variable explains 96.9% of the variation in youth moral development, while the rest (3.1%) is influenced by other factors outside the research model. The implications of this study emphasize the importance of churches to continue to strengthen and integrate PAH programs, counseling, and pastoral ministry as the main strategies in fostering youth morality. Recommendations include improving the quality of relevant PAK curriculum, strengthening the capacity of counselors and pastoral pastors, and creating a church environment that supports the moral growth of youth holistically. This research is expected to make a significant contribution to practical theology, Christian education, and youth ministry strategies in the context of Pentecostal churches and other denominations.